Teaching Reading Narrative Text by Using Directed Inquiry Activity (DIA) Technique at Junior High School - Ahmad Hamidi; Aryuliva Adnan (Journal of English Language Teaching, 2013)
AbstractReading is one of the English skills taught at all different levels of education. There are various texts that should be mastered by students. They are transactional dan interactional, monologue, and short functional text. One of monologue texts found at the junior high school level is a narrative text. Students of Junior High School are expected to comprehend this text very well; however, there are still students who do not have good comprehension of this text. This might be caused by the students themselves or by the uninteresting techniques used by teachers to teach this text. Among the techniques applied to teach narrative texts, there is DIA (Directed Inquiry Activity) which is expected to help increase the students’ comprehension of the texts. This technique provides students with activities directing them to develop their own comprehension by using their own efforts. Teachers will explain some difficult vocabularies to the students and through a class discussion, the students are going to answer the questions and do the inquiries to the generic structure of the text. Kata kunci : Teaching Reading, Narrative Text, Directed Inquiry Activity (DIA)